2009
DOI: 10.1086/598844
|View full text |Cite
|
Sign up to set email alerts
|

Teacher‐Parent Relationships and School Involvement among Racially and Educationally Diverse Parents of Kindergartners

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(60 citation statements)
references
References 18 publications
0
54
0
1
Order By: Relevance
“…For example, better quality parent-provider relationships are linked to parents' satisfaction with services (Kontos & Dunn, 1989), parent involvement (Elicker, Noppe, Noppe, & Fortner-Wood, 1997;Nzinga-Johnson, Baker, & Aupperlee, 2009), parental self-efficacy beliefs (Green, McAllister, & Tarte, 2004;Trivette, Dunst, & Hamby, 2010), and the quality of parent-child relationships (Dunst, 2002;Elicker, Wen, Kwon, & Sprague, 2013;Heinicke et al, 2000).…”
Section: Family-provider Relationships and Child And Family Outcomesmentioning
confidence: 99%
“…For example, better quality parent-provider relationships are linked to parents' satisfaction with services (Kontos & Dunn, 1989), parent involvement (Elicker, Noppe, Noppe, & Fortner-Wood, 1997;Nzinga-Johnson, Baker, & Aupperlee, 2009), parental self-efficacy beliefs (Green, McAllister, & Tarte, 2004;Trivette, Dunst, & Hamby, 2010), and the quality of parent-child relationships (Dunst, 2002;Elicker, Wen, Kwon, & Sprague, 2013;Heinicke et al, 2000).…”
Section: Family-provider Relationships and Child And Family Outcomesmentioning
confidence: 99%
“…In addition to the lack of a conceptual framework for understanding parent-teacher relationships, much of the research on parent-teacher relationships has focused on older children (Bernhard et al, 1988;Nzinga-Johnson et al, 2009). Far less is known about parent-teacher relationships for infants and toddlers.…”
Section: Parent-teacher Relationshipsmentioning
confidence: 99%
“…Bronfenbrenner's (1977) ecological systems theory outlines the potential developmental impact of connections and experiences across different microsystems (e.g., home and childcare), or what Epstein (1995) later referred to as "spheres of influence," in a child's life. Using this understanding, some researchers have attempted to examine the connections across home and school or childcare settings by identifying the influences, outcomes, and make-up of strong versus conflictual parent-teacher relationships (Bernhard et al, 1988;Forry, Moodie, Simkin, & Rothenberg, 2011: McGrath, 2007Nzinga-Johnson, Baker, & Aupperlee, 2009).…”
mentioning
confidence: 99%
“…This is no different in a racially diverse school. Studies have shown that socioeconomic and cultural/ethnic factors do significantly contribute to the lack of quality in the parent-teacher relationship (Nzinga-Johnson, Baker, and Aupperlee, 2009). Racism may play a role in the parent"s sense of acceptance, and in their feelings towards the school or teacher, so an extra effort must be made to cross those barriers.…”
Section: Schools Have Struggled With This Task Of Communication For Ymentioning
confidence: 99%